(untitled) (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: To analyze the presence of selective antibiotic residues (oxytetracycline, amoxicillin, and ciprofloxacin) in milk during the antibiotic treatment course, and to evaluate the thermal effect on antibiotics residual status in milk of antibiotic-treated cows. Materials and Methods: The raw fresh milk was collected from 18 lactating cows before antibiotics treatment, which were brought to the veterinary hospital and suffered from either mastitis, foot and mouth disease, fever, local wound, or non-specific diarrhea, and so on. Out of the 18 lactating cows, six were treated with oxytetracycline, six were treated with amoxicillin, and six were treated with ciprofloxacin parenterally. Milk samples were also collected at 2nd day during treatment and final collection was done after maintaining the withdrawal period. Since milk is heated before consumption, it was boiled at 100°C for 20 min to evaluate the thermal effect on antibiotics residual status. Thin-layer chromatography was done for screening of antibiotics residue before and after boiling of the milk. Results: At day 0 (before antibiotic treatment), no antibiotics (oxytetracycline, ciprofloxacin and amoxicillin) residue was detected in raw milk of antibiotic treated cows. In contrast, on day 2 (during antibiotic treatment), 100% raw milk samples showed positive for antibiotics residue. After boiling, all milk samples showed positive for such specific antibiotics residue. On the other hand, no antibiotics residues were detected on day 9, which indicates the completion of the withdrawal period of the respective antibiotic. The intensities of bands for antibiotic on thin-layer chromatography plate of antibiotic residues in milk samples (oxytetracycline, amoxicillin, and ciprofloxacin) expressed that the respective antibiotic residual status was higher in the boiled milk compare to the raw milk. Conclusion: Proper maintenance of withdrawal period after antibiotic treatment would minimize the risk of antibiotic residues in milk, and boiling does not change these specific antibiotics residual status in milk. Therefore, awareness regarding the proper maintenance of withdrawal period after antibiotic treatment in lactating cows is one of the best strategies that may positively reduce the risk of antimicrobial drugs residue in milk. J. Adv. Vet. Anim. Res., 6(4): 516-520, December 2019